(untitled) (Journal of the College of Basic Education, 2025)
In this study, extracts were prepared from Ficus carica fruits and latexes, and then estimate the cytotoxic activity of these extracts on cancer and normal cell lines. Brest cancer (Ahmed, Murtudha, Jabriyah, 2013 (AMJ13)) and Brain cancer (A human glioblastoma multiforme (ANGM)) cancer cell lines and Rat Embryo Fibroblast (REF) normal cell line were used in the in vitro study. Normal cell line was measured after only 72 hours of exposure while cancer cell line exposure times were estimated after (24, 48, and 72) hours under sterile conditions in a micro titration plate. Anti-cancer property of Ficus carica extracts on cancer cells has been reported and there was no effect on normal cells. In this work, the AMJ13, ANGM and REF cell line were treated with six concentrations of two type of F. carica extract (31.25, 62.5, 125, 250, 500 and 1000 μg/mL). The anticancer effect of F. carica extracts was measured using the microculture tetrazolium assay (MTT). The result obtained showed concentration and time dependent cytotoxic effect also the type of cell line effect on the result, the higher concentrations (1000 μg/mL) of extracts gave significantly (p<0.05) higher cytotoxic effect on cancer cell lines at 48 hours of exposure.